Evaluating Iraqi Primary EFL Curriculum and Textbooks - Alkhateeb, Muna Mohammed Abbas (JPAIR Multidisciplinary Research, 2013)
A textbook is an organized collection of designed material. In Iraq, “Iraq Opportunities” series from Third till Sixth primary grades, Activity book, Teacher’s book, and Curriculum Document, were all prescribed by the Ministry of Education. In order to determine whether textbooks writers are currently meeting the Educational objectives, certain units of the four books being analyzed in terms of a range of effective criteria derived from relevant sections of the curriculum Document. To achieve this, the researcher evaluated the Curriculum Document, the Textbooks, Teacher’s Book and Activity Books to find out whether they match with the expected standards according to Nation’s principles. From the analysis, we have gotten the language content is generally consistent with the Grades 3-6 curriculum Document objectives.
Keywords: Nation’s twenty principles; Curriculum Document; EFL teaching materials; Primary curriculum and textbook in Iraq